The Influence of Corporate Psychopaths on Corporate Social Responsibility and Organizational Commitment to Employees - Boddy, Clive R.; Ladyshewsky, Richard K.; Galvin, Peter (2010)
This study investigated whether employee perceptions of corporate social responsibility (CSR) were associated with the presence of Corporate Psychopaths in corporations. The article states that, as psychopaths are 1% of the population, it is logical to assume that every large corporation has psychopaths working within it. To differentiate these people from the common perception of psychopaths as being criminals, they have been called “Corporate Psychopaths” in this research. The article presents quantitative empirical research into the influence of Corporate Psychopaths on four perceptual measures of CSR and three further measures of organizational commitment to employees. The article explains who Corporate Psychopaths are and delineates the measures of CSR and organizational commitment to employees that were used. It then outlines the research conducted among 346 corporate employees in Australia in 2008. The reliability of the instrument used is commented on favorably in terms of its statistical reliability and its face and external validity. Results of the research are described showing the highly significant and negative influence of Corporate Psychopaths on all of the measures of CSR and of organizational commitment to employees used in the research. When Corporate Psychopaths are present in leadership positions within organizations, employees are less likely to agree with views that: the organization does business in a socially desirable manner; does business in an environmentally friendly manner and that the organization does business in a way that benefits the local community. Also, when Corporate Psychopaths are present in leadership positions within organizations, employees are significantly less likely to agree that the corporation does business in a way that shows commitment to employees, significantly less likely to feel that they receive due recognition for doing a good job, to feel that their work was appreciated and to feel that their efforts were properly rewarded. The article argues that academics and researchers in the area of CSR cannot ignore the influence of individual managers. This is particularly the case when those managers have dysfunctional personalities, or are actually psychopaths. The article further argues that the existence of Corporate Psychopaths should be of interest to those involved in corporate management and corporate governance because their presence influences the way corporations are run and how corporations affect society and the environment.
Keywords: Corporate Social Responsibility; Morals; Corporate Psychopaths; Leadership